Ventricular interdependence in critically ill patients: from physiology to bedside - Petit, Matthieu; Vieillard-Baron, Antoine (Frontiers in Physiology, 2023)
The review focuses on the mechanism of ventricular interdependence, a frequently encountered phenomena, especially in critically ill patients. It is explained by the anatomy of the heart, with two ventricles sharing a common wall, the septum, and nested in an acutely inextensible envelope, the pericardium. In pathological situation, it results in abnormal movements of the interventricular septum driven by respiration, leading to abnormal filling of one or the other ventricle. Ventricular interdependence has several clinical applications and explains some situations of hemodynamic impairment, especially in situations of cardiac tamponade, severe acute asthma, right ventricular (RV) overload, or more simply, in case of positive pressure ventilation with underlying acute pulmonary hypertension. Ventricular interdependence can be monitored with pulmonary arterial catheter or echocardiography. Knowledge of this phenomena has very concrete clinical applications in the management of filling or in the prevention or treatment of RV overload.